Exploring the Impact of Kernel Function and Bandwidth Parameters on Covariate Estimates - Mansurov Dilshod Ravilovich; Sherkulova Sabina Lochin kizi (Genius Journals, 2023)
In this article we are exploring the impact of kernel function and bandwidth parameters on covariate estimates
Keywords: Kernel function